Application of advanced oxidation processes to wastewater treatment - Lucas, Marco Paulo Gomes de Sousa (2009)
This research contributes to the study and development of advanced oxidation technologies applied to two different problematic wastewaters: textile and winery wastewaters. In this dissertation the factors that influence the oxidation of the model compound of textile wastewaters, the azo dye Reactive Black 5 (RB5), and of the winery wastewaters were investigated. The first part of the thesis experimental work is dedicated to the decolorization of RB5 solutions. The RB5 dye was selected as model molecule to represent the concerned dye group because is widely used in the textile and paper industries, hardly biodegradable and inexpensive. Firstly, an experimental comparison among two photoxidation systems, Fenton/UV-C and ferrioxalate/H2O2/solar light, was performed. The variables considered were pH, H2O2 dosage, iron dosage, RB5 concentration and source of light. The experiments indicate that RB5 can be effectively decolorized using Fenton/UV-C and ferrioxalate/H2O2/solar light processes with a small difference between the two processes, 98.1 and 93.2%, respectively, after 30 minutes. Although the lesser difference in dye decolorization, significant increment in TOC removal was found with Fenton/UV-C process (46.4% TOC removal) relative to ferrioxalate/H2O2/solar light process (29.6% TOC removal). This fact reveals that UV-C low pressure mercury lamp although with its small effect on dye decolorization is particularly important in dye mineralization, when compared to solar light. Further, it was tested the decolorization of aqueous azo dye RB5 solution combining an Advanced Oxidation Process (Fenton’s reagent) followed by an aerobic biological process (mediated by the yeast Candida oleophila). Fenton’s process alone, as well as aerobic treatment by Candida oleophila alone, exhibited the capacity to significantly decolorize azo dye solutions up to 200 mg/L, within about 1 and 24 hours respectively. By contrast, neither Fenton’s reagent nor Candida oleophila sole treatments showed acceptable decolorizing abilities for higher initial dye concentrations (300 and 500 mg/L). But the combination between the two processes, with Fenton’s reagent process as primary treatment, at 1.0x10-3 mol/L H2O2 and 1.0x10-4 mol/L Fe2+, and growing yeast cells as a secondary treatment, achieves a color removal of about 91% for an initial RB5 concentration of 500 mg/L. In a second stage, is presented the experimental work done with winery wastewaters. This study starts with the evaluation of the capacity of different Advanced Oxidation Processes (AOP) combined with several radiation sources to degrade the phenolic compound Gallic Acid (GA), the most representative phenolic compound present in the winery wastewaters. From the experiments conducted it was possible to suggest that the AOP, Fe2+ + H2O2 + UV TNN 15/32 (photo-Fenton process), was the most efficient process thereby achieving the GA degradation value of 95.6% in 7.5 minutes and resulting in a total elimination of toxicity. Afterwards, the degradation of simulated winery wastewater was studied in a pilotscale Compound Parabolic Collector (CPC) solar reactor. Total organic carbon (TOC) reduction with heterogeneous photocatalysis (TiO2) and homogeneous photocatalysis with photo-Fenton is observed. Heterogeneous photocatalysis with TiO2, TiO2/H2O2 and TiO2/S2O8 2- is revealed to be inefficient in removing TOC, achieving TOC degradation of 10%, 11% and 25%, respectively, at best. However, photo-Fenton experiments achieved 46% TOC degradation in simulated wastewater prepared with diluted wine (WV) and 93% in wastewater prepared with diluted grape juice (WG), and if ethanol is previously eliminated from mixed wine and grape juice wastewater (WW) by air stripping, it removes 96% of TOC. Ozonation of organic substances present in winery wastewater was studied in a pilot-scale bubble column reactor. A steady reduction of chemical oxygen demand (COD) was observed under the action of ozone at the natural pH of the wastewater (pH 4). At alkaline and neutral pH the degradation rate was accelerated by the formation of radical species from the decomposition of ozone. The monitoring of pH, redox potential (ORP), UV absorbance (254 nm), polyphenols content and ozone consumption was correlated with the oxidation of the organic species in the water. The ozonation of winery wastewater in the bubble column was analysed in terms of a mole balance coupled with ozonation kinetics modeled by the two-film theory of mass transfer and chemical reaction. It was determined that the ozonation reaction can develop both in and across different kinetic regimes: fast, moderate and slow, depending on the experimental conditions. Besides ozonation also the effectiveness of different ozone-based advanced oxidation processes (O3, O3/UV and O3/UV/H2O2) on the treatment of winery wastewater was investigated in the same pilot-scale bubble column reactor. In all the experiments the disappearance of the winery wastewater organic load was described by pseudo-first order apparent reaction kinetics. The faster rate constant (6.5 x 10-3 min-1), at the natural pH of the wastewater, was observed with the O3/UV/H2O2 process under optimised oxidant dose (COD/H2O2 = 2). An economical analysis on the operating costs of the AOPs processes investigated revealed the O3/UV/H2O2 to be the most economical process (1.31 Euro m-3g-1 of TOC mineralised under optimised conditions) to treat the winery wastewater. Finally, the degradation of the organic pollutants present in winery wastewater was carried out by the combination of two successive steps: a long term aerated storage bioreactor followed by a chemical oxidation process using Fenton’s reagent. The long term hydraulic retention time, 11 weeks, contributed remarkably to the reduction of COD (about 90%) and the combination with the Fenton’s reagent led to a high overall COD reduction that reached 99.5% when the mass ratio (R=H2O2/COD) used was equal to 2.5, maintaining constant the molar ratio H2O2/Fe2+=15.